Teaching clinical trials electronically - Ostbye, Truls; Deonandan, Raywat; Donner, Allan; Sim, Dalice (Université d'Ottawa | University of Ottawa, 1999)
This ar ticle discusses the development, delivery and evaluation of an electronic extramural course, `Fundamentals of Clinical Tr ials’ , a CME course designed to reach physicians and health care researchers without easy access to a local university. Ten week-long modules of instruction were developed.These were based on a graduate course in clinical tr ials, standard textbook topics and additional course mater ials speci® cally developed for the course. Questions and course topics were to be discussed by the students, and each participant was encouraged to present an actual or proposed clinical tr ial to the vir tual class. Communication between students and tutors could be either `one to one’ or through a listserve, i.e. an automated mailing list available to all participants which copied and routed any message instantly to all participants. Ongoing evaluation of the course was accomplished by questions monitoring students’ attitudes and needs, and a more extensive on-line questionnaire administered at the end of the course. Ten students from four countr ies were accepted onto the course. Half of the students contr ibuted regularly and extensively, while the others tended to respond only when addressed directly.The students spent on average approximately 6 hours per week on the course. This differed little from regular classroom courses, but the students appreciated the ability to organize the course around their regular schedules.The students prefer red topics that encouraged discussion and differ ing opinions. From the instructors’ viewpoint, considerable time was required for course development and communication.This form of distance continuing medical education was preferr ed by all the students over regular cor respondence courses, as it allowed for more immediacy and interaction.However, the time required for developing and teaching courses over the Internet should not be underestimated.